Lớp phủ bảo vệ chống ăn mòn trên cơ sở epoxy với sự có mặt của polyindol lai tạp axit indol-3 butyric - Trúc, Trịnh Anh; Anh, Lê Kim; Lê Hiền, Nguyễn Thị; Xuân Hằng, Tô Thị (Vietnam Journal of Chemistry, 2014)
This study is focused on the synthesis of a polyindole doped by indole-3 butyric acid (PI-IBA). IR analyze indicated that the linkage positions of indole involves the position 2 and 3 of the monomer and the insertion of IBA in the polymer backbone. Polyindole IBA doped was incorporated into epoxy resin for protection anticorrosion of carbon steel. The electrochemical impedance measurements show a significantly improvement of protective properties in presence of PI-IBA in comparison with pure epoxy and epoxy containing polyindole coating. The local electrochemical impedance measurements show the self healing capacity of coating containing PI-IBA. In this case, this conducting polymer acts as a smart paint releasing inhibitors on demand by the redox reaction between polyindole and metal surface